The twenty-one balloons - Du Bois, William Pene, 1916- (New York : Viking Press, 1975)
Professor William Waterman Sherman, a disillusioned school-teacher, sets sail in a giant balloon, determined to circumnavigate the globe. His adventure takes a wild turn when he crash-lands on the notorious island of Krakatoa, where he discovers a strange and wonderful culture and untold riches, and where he witnesses the volcanic explosion that destroys the entire island. When he is found adrift in the Atlantic clinging to the wreckage of a huge balloon airship, America is rocked by curiosity, which turns to amazement as his fantastic tale unfolds.
Keywords: Balloons -- Fiction; Voyages and Travels -- Fiction; Krakatoa (Indonesia) -- Eruption, 1983